Antimicrobial treatment in invasive infections caused by Gordonia bronchialis: systematic review - Zivkovic Zaric, Radica; Canovic, Petar; Zaric, Milan; Vuleta, Marko; Vuleta Nedic, Katarina; Jovanovic, Jovan; Zornic, Nenad; Nesic, Jelena; Spasic, Marko; Jakovljevic, Stefan; Ilic, Milena; Jovanovic, Dalibor; et al. (Frontiers in Medicine, 2024)
Background: Corynebacterium, Nocardia, Rhodococcus, Mycobacterium, as well as Gordonia genera belongs to the genus Gordonia, Actinomycetia class. Gordonia bronchialis is a nitrate-reducing, urease-producing, non-motile, force aerobe with a rod-like figure that is known to arrangement into sessile, cord-like groups. This systematic review aimed to establish whether and what invasive infections in humans were caused by Gordonia bronchialis, and to evaluate outcomes of administered antibiotic treatment. Method: We have registered this systematic review in PROSPERO database of systematic reviews and meta-analyses with the number CRD42022369974. Results: A total of 24 publications were included (22 case reports and two case series) with 28 individual cases. The oldest patients had 92 years, and the youngest patients had 13 years. Clinical signs of infection were present in 6 patients (21%). All isolates were susceptible to ciprofloxacin, imipenem and amikacin. Vancomycin was the most frequently used antibiotic with 9 cases followed by ciprofloxacin, ceftriaxone, and amoxicillin/clavulanic acid. Conclusion. Although there are no standardized recommendations to date, successful treatment with a favorable outcome has most often been carried out with fluoroquinolones, vancomycin with or without aminoglycosides, as well as carbapenems.